O significado do trabalho de parto e parto para os alunos de enfermagem da Universidade Federal do Ceará - Carvalho, Francisca Ana Martins (2005)
In practice obstetric, the graduation student in Nursing faces difficulties when exercising the care to the parturient because same tends theoretical knowledge, it is sametimes inert to the direct cares that they should be rendered the woman um labor and childbirth. When accomphishing my study objective it was to understand the meaning of labor and childbirth for the student of Nursing that experiences the discipline Nursing in the Process of Taking Care III – Woman, of the Federal University of Ceará (UFC). For so much, I opted for the qualitative approach and for the theoretical perspective of symbolic Interacion. They participated in the study twenty graduation students in Nursing that they were developing the obstetric practice in the Center of Normal Childbirth of the Maternity – School Assis Chateaubriand of UFC, during the months of abril to june of 2004. The collection of data, was utilized the participant observation, the fields diaries and the interview open with the following question: Which the meaning of the labor and childbirth for you after having witnessed it?. With base in the analysis of Bardin (2000) and in the theoretical relate in Symbolic Interaction, it was possible understanding the meaning of the labor and childbird for the Nursing’s student of UFC begging with the following questions: To witness the plysical and emotional suffering lived by the parturient; To face the insecurity in attending the parturient; and Birth – the discovery of a new life. As I undestood, independent experiences the student’s Nursing living the obstetric practice, interacting with the woman in the labor and childbirth, checking, containing and interpreting the senses and meanings of the parturition process. At the same time, with the influence of parturiation process, motivation them, to see the childbirth first, and this became sensible, to act and to take care of the woman in labor and childbirth. As Nurses, who teaching at the University, working in the hospital and other one, should put ourselves in the student’s same condition, looking for to discover a walk didactic – pedagogic capable to make possible a favorable atmosphere to a bether care of Nursing to the woman in parturition process, valuing the knomledge, the relation of the science and the professional autonomy.